The protective role of social support on prenatal depression among pregnant women of advanced maternal age: a Three-Trimester follow-up study in China. (17th November 2022) - Liu, Shaofei; Lin, Qiaoxuan; Feng, Yonghsen; Zhong, Dongmei; Jiang, Cuiting; Zhang, Lifeng
Abstract: The aim of this study was to compare the depressive symptoms during pregnancy between pregnant women aged over 35 years and those aged less than 35 years and to evaluate the protective effect of social support in early pregnancy against prenatal depressive symptoms. One hundred and seventy one women aged over 35 years and 342 trimester-matched women aged less than 35 years were included from a level III hospital in Shenzhen, China. The self-report Edinburgh Postnatal Depression Scale (EPDS) and Social Support Rating Scale (SSRS) were used to evaluate prenatal depression and social support in early pregnancy. The proportions of women aged over 35 years who screened positive for prenatal depression were 22.8%, 23.4%, and 24.0% in the first, second and third trimesters, respectively. Advanced maternal age (≥35 years) was a positive predictor of prenatal depressive symptoms ( β  = 0.747, P  = 0, 008). Social support, especially objective support ( β  = -0.030, P  = 0.002) and subjective support ( β  = -0.028, P  = 0.006) in early pregnancy, had stronger protective effects against prenatal depressive symptoms for women aged over 35 years than younger women. Our findings support that older pregnant women experience more depressive symptoms than younger pregnant women, and social support could serve as a targeted intervention to decrease prenatal depressive symptoms. Impact statement: What is already known on this subject? Depressive symptoms, which are strongly associated with adverse psychosocial and birth outcomes, appear to be prevalent and change in nature. Social support is an important protective factor against prenatal depression. What the results of this study add? Pregnant women of advanced maternal age experienced more depressive symptoms than younger women during the prenatal period. Social support, especially objective support and subjective support, had stronger protective effects against prenatal depression for women aged over 35 years than women aged less than 35 years. What the implications of these findings are for clinical practice? Screening of prenatal depression should be strengthened, especially for women aged over 35 years, and improving subjective support could improve their emotional experience.